Pengaruh Hubungan Laki-laki Seks dengan Laki-Laki dengan Munculnya Risiko Infeksi Menular Seksual Pada Pria Perilaku Seksual Promiskuitas - Robert Kosasih; Dean Ascha Wijaya; Fernando Nathaniel; Yohanes Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2023)
Sexually transmitted infections (STIs) are still a problem in Indonesia because the numbers are always increasing every year. STIs create a burden of morbidity and mortality and directly impacts a person's quality of life and reproductive health. This cross-sectional study aims to determine the relationship between sexuality and the incidence of STIs, which were selected consecutively using medical record data at one of the Primary Clinics in Jakarta from August 2022 to May 2023. The variables in this study were history of sexuality and current incidence of STIs at the time of the investigation. Statistical analysis using the Fisher Exact test. Of the 114 respondents, the average age was 30.93 years and 8.8% of respondents were positive for STIs status. The type of high-risk patient is non-MSM by 62.3%. The results of the Fisher Exact statistical test found that there was a significant relationship for the occurrence of STIs in the group of men with a tendency to be MSM (p-value: 0.040). Based on the data that has been analyzed, the group of men with a predisposition to MSM has a 3.853 times higher risk of being positive for STIs than the group of men without MSM.